PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 015 TANJUNG LEBAN KECAMATAN KUBU KABUPATEN ROKAN HILIR - Syafri, Edi; Daud, Damanhuri; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. The rescearch is cause is the low social studies students learning outcomes with average grade 56. While the udue of minimum criteria of completenes is 65 this researches is classroom action research (CAR). That suppose to incriasing of the social studies students learning outcomes of fourth grade of elementery school 028 Sintong Tanah Putih in Rokan Hilir district. The formula of the problem is does the aplication of cooperative learning model type two stay two stray (TSTS) can inprove the social studies studen learning outcomes of fourth grade SDN 015 Tanjung Leban Kubu in Rokan Hilir District. Before dairy CAR the students good average grade 56. Ard after CAR the average grade in create is 66% whereas on the scord cycle the average grade increase is 71,5. So the improvement of students learning out comes from the bassed score to cycle I increase about 17,85% whereas from based score to cycle II increase about 27,67%. The activity of the student in first cycle with an average grade 50% and the scord cycle is about 66,66%. The activity of the teacher on the first cycle with an average grade 58,33% and the secord cycle is about 70,83%. The result of this research is the application of cooperative learning model type examples non examples can increase the social studies students learning outcomes at fourth brade of elementary 015 Tanjung Leban Kubu in Rokan Hilir District.Key Word : Kooperative type examples non examples The social student achievement